(untitled) (CIPEEX, 2026)
Introduction: The skin is the largest organ in the human body and performs functions of protection, regulation, and cellular communication. Aging and environmental factors promote visible structural changes, such as wrinkles and dryness. Nutrition plays a relevant role in health, and supplementation with collagen peptides has been associated with improved elasticity, hydration, and wrinkle reduction, although more evidence is needed. Objective: To evaluate the effects of oral supplementation with Verisol® hydrolyzed collagen (2.5 g/day) on expression lines and skin quality in the orbicularis oculi region of middle-aged women. Method: Fifty women aged 35 to 58, sedentary for at least one year, were recruited. Consumers, users of protein supplements, restorative cosmetics, or those undergoing cosmetic procedures were excluded. Volunteers received 2.5 g/day of Verisol® collagen for three months. Weight, height, BMI, body composition, dietary intake, and characteristics (hydration, oiliness, and specifications) were assessed using specific equipment. Statistical analysis used GraphPad Prism 5.0, with paired and unpaired Student’s t-test (p<0.05). Results: Supplementation did not alter the number of wrinkles or apparent oiliness, but significantly reduced wrinkle length (p<0.0216) and increased skin elasticity (p<0.04). Hydration showed no differences between groups. Conclusions: Supplementation with 2.5 g/day of Verisol® collagen for 12 weeks promoted a reduction in wrinkle length and improved periorbital skin elasticity in middle-aged women. Keywords: skin; collagen; supplementation; wrinkles.